Cartilla: Como comprar y vender bienes registrables - Cramero, Paulina; Abraham, Pamela; Pithod, Julián; Scherbosky, Roberto Isaac (coordinador) (EEA La Consulta, INTA, 2025)
Documento bilingüe en español y quechua